1996
DOI: 10.1007/bf02637097
|View full text |Cite
|
Sign up to set email alerts
|

The structure‐activity relationship of lipoxygenase products of long‐chain polyunsaturated fatty acids: Effects on human platelet aggregation

Abstract: The effect of hydroperoxy and hydroxy derivatives of various fatty acids on human platelet aggregation was determined to delineate potencies and structure-activity function. In this regard, the 22-carbon n-3 fatty acids are the most potent inhibitors in comparison to the n-6 lipoxygenase derivatives. Submicromolar levels of the docosapentaenoic (22:5) and especially docosahexaenoic (22:6) n-3 hydroperoxy and hydroxy derivatives specifically antagonize the platelet aggregating effect to arachidonic acid (AA, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Docosapentaenoic acids, 22:5n-3 and 22:5n-6 are also good substrates of platelet 12-LOX, and the former behaves like DHA with its conversion into 11-and 14-OH derivatives, whereas 22:5n-6 is only converted into 14-OH-22:5 [33]. Both metabolites from 22:5n-3 were shown to inhibit the ArA-induced platelet aggregation [34]. Although 22:5n-3 is generally considered as a minor omega-3 PUFA in marine sources, compared to DHA and EPA, it may increase in vivo as a result of EPA elongation.…”
Section: Oxygenation Of Ara In Human Blood Plateletsmentioning
confidence: 98%
“…Docosapentaenoic acids, 22:5n-3 and 22:5n-6 are also good substrates of platelet 12-LOX, and the former behaves like DHA with its conversion into 11-and 14-OH derivatives, whereas 22:5n-6 is only converted into 14-OH-22:5 [33]. Both metabolites from 22:5n-3 were shown to inhibit the ArA-induced platelet aggregation [34]. Although 22:5n-3 is generally considered as a minor omega-3 PUFA in marine sources, compared to DHA and EPA, it may increase in vivo as a result of EPA elongation.…”
Section: Oxygenation Of Ara In Human Blood Plateletsmentioning
confidence: 98%
“…This hypothesis was explored extensively after the early reports that cyclooxygenase products of DHA were produced in the rainbow trout gill (79). Early investigations indicated that products made by rat brain were sensitive to LO inhibitors (80)(81)(82)(83). A correction of the trout gill work indicated that the DHA products were not prostaglandins but rather LO products (84).…”
Section: Mechanisms Of Action Of Dhamentioning
confidence: 99%
“…Platelets are surrounded by plasma membrane and they have intensive intracellular membrane systems like the dense tubular system. Alterations in the precursor FA pool may also affect platelet function via lipoxygenase products [12]. Phospholipid FA composition may have effects on the physicochemical properties of the cell membranes which can cause alterations in receptor activities and intracellular signalling.…”
Section: Dietary Fatty Acids and Platelet Functionmentioning
confidence: 99%